Potential allelopathic rice lines for weed management in Cambodian rice production - Pheng, Sophea; Olofsdotter, Maria; JAHN, GARY; Adkins, Steve W. (Wiley, 2009)
In Cambodia, the planting of rice lines with a competitive and/or allelopathic ability would be a very useful way to supplement weed management in the rain‐fed, low‐input production systems. The present study examines a wide range of rice germplasm, mainly from Cambodia, and uses a series of bioassay techniques to identify those that might have a weed growth‐suppressing, allelopathic trait. A laboratory bioassay study that involved 359 rice lines showed that there were 15 that could significantly reduce the growth of awnless barnyard grass seedlings. In a second laboratory bioassay, involving the best 96 rice lines that were identified in the first study, 14 were shown to suppress the shoot growth of awnless barnyard grass, 11 could suppress the shoot growth of barnyard grass, six could suppress the shoot growth of small umbrella sedge, four could suppress the shoot growth of two‐leaf fimbristylis, four could suppress the shoot growth of water primrose, and three could suppress the shoot growth of gooseweed. Of the 13 rice lines that were able to suppress the growth of at least two weed species, there were three lines that could suppress the growth of three weed species, one line that could suppress the growth of four weed species, and one line that could suppress the growth of five weed species. In a third soil‐based, pot bioassay that studied the 18 best lines coming from the second laboratory bioassay, all showed a significant weed growth‐suppressive ability. A linear regression analysis showed that there was no correlation between their weed growth‐suppressive ability and their physical seedling size, supporting the idea that the growth suppression was allelopathic in nature and not a physical competition effect. In summary, the results indicate that an allelopathic trait does exist in some Cambodian rice lines and that this trait is effective in the growth suppression of a number of major rice weeds.